Pengaruh Lingkungan Kerja Fisik Dan Budaya Organisasi Terhadap Produktivitas Karyawan Pada Yayasan Prima Mentari Di Kabupaten Tangerang - Verren Yehezkiel; Endang Suprapti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This study aims to determine the effect of physical work environment and organizational culture on employee productivity at yayasan prima mentari kabupaten tangerang, both partially and simultaneously. This research uses quantitative methods with a saturated sample of 55 respondents. Data analysis techniques include instrument tests, classical assumption tests, linear regression, correlation, determination, and hypothesis testing (t-test and F-test). The results show: (1) Physical Work Environment partially has a positive effect on productivity (Y = 19.899 + 0.561X1). Correlation value is 0.627 (strong) and determination is 39.3%. This is evidenced by t count > t table (5.911 > 2.006) and sig < 0.05. (2) Organizational Culture partially has a positive effect on productivity (Y = 8.278 + 0.804X2). Correlation value is 0.758 (strong) and determination is 57.5%. This is evidenced by t count > t table (8.544 > 2.006) and sig < 0.05. (3) Simultaneously, Physical Work Environment and Organizational Culture have a positive effect on productivity (Y = 6.716 + 0.222X1 + 0.639X2). Correlation value is 0.782 (strong) and determination is 61.2%. This is evidenced by F count > F table (41.788 > 3.172) and sig < 0.05